Analisis Kesulitan Memahami Teks Bacaan Bahasa Jawa Pada Siswa SD Negeri Pesantunan 01 - Rizqiah, Naila; Laelia Nurpratiwiningsih; Atikah Mumpuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the forms of difficulties in understanding Javanese reading texts experienced by fourth-grade students at SD Negeri Pesantunan 01. This study employed a qualitative approach with a case study design. Data were collected through structured interviews, observations, tests, and documentation. The data sources consisted of six fourth-grade students and the fourth-grade classroom teacher at SD Negeri Pesantunan 01. The findings revealed four forms of difficulties experienced by students: (1) difficulty understanding Javanese vocabulary; (2) difficulty distinguishing between Ngoko and Krama language varieties; (3) difficulty understanding the overall content of reading texts; and (4) difficulty drawing conclusions and retelling the content of the texts. The findings indicate that limited vocabulary mastery is the main factor affecting students’ reading comprehension ability.